“From Large-Scale Collections to the Potential Use of Genomic Techniques for Supply of Drug Candidates” - Newman, David J. (Frontiers in Marine Science, 2018)
The initial sources of compounds that on a small scale exhibited interesting biological activities were confined to medium (a few kilograms) to larger scale (up to 100 kilograms or more) of the nominal source organism. Over the last 10 plus years, this paradigm has moved to semisynthesis, total synthesis (sometimes of simpler versions) and the use of genomic techniques both to identify the "source" and then to utilize the data in due course. Examples will range from the early days with the arabinose-containing nucleosides, didemnins, through the ecteinascidins and halichondrins, and then to more current molecules derived from dolastatins that are now used as “warheads."